The challenge of compassion in predator conservation - Pooley, Simon (Frontiers in Psychology, 2022)
This paper addresses the need for compassion in conservation science through the lens of human-wildlife conflicts and coexistence. It uses seven case studies of human-crocodilian interactions, including attacks by Nile crocodiles in southern Africa and mugger crocodiles in Gujarat in India, to demonstrate the challenges of conserving dangerous predators and the need for compassion for those who suffer traumatic encounters with them. It notes that compassion for wild animals sometimes appears to be in conflict with compassion for the humans living alongside them. It draws on some approaches to animal ethics to consider if there is a way beyond the apparent impass in conservation where compassion for individual animals paralyses conservation action. The paper concludes with thoughts on the role of compassion in fostering human-wildlife coexistence, and notes some implications of taking a compassionate approach to conservation interventions.